Faktor yang mempengaruhi minat beli online Produk Makanan dan Minuman UKM. Studi pada masyarakat Kabupaten Bandung Barat, Indonesia - Irfania, Novi (International Journal Administration, Business & Organization, 2022)
Advances in technology make online shopping models increasingly in demand by the public. This change in spending behavior has made the government seek to digitize the UMKM sector. However, only 3.79 million UMKMs have used online platforms to market their products. Therefore, this study was conducted with the aim of knowing the factors that influence Kabupaten Bandung Barat society’s online purchase intention on UMKM’s food and beverage products and knowing the magnitude of the influence of each factor. So it is hoped that this research can help UMKMs develop their business through online media. This study uses a quantitative descriptive method. The respondents obtained were 101 of Kabupaten Bandung Barat’s society. Data were analyzed using SPSS v.26 using factor analysis and multiple regression analysis. The results of this study indicate that online purchase intention consists of four factors, there are information value, media display, price, and trust. All factors together or partially have a positive influence on the online purchase intention of UMKM’s food and beverage products in Kabupaten Bandung Barat.